Design of highly stretchable deep eutectic solvent‐based ionic gel electrolyte with high ionic conductivity by the addition of zwitterion ion dissociators for flexible supercapacitor. Issue 1 (23rd October 2020) - Bu, Ximan; Ge, Yongxin; Wang, Lei; Wu, Linlin; Ma, Xiaofeng; Lu, Duyou
Abstract: Nonvolatile deep eutectic solvent (DES) electrolytes with good electrochemical stability have recently emerged as promising electrolytes for energy storage devices. In this report, for the first time a polymerized zwitterionic molecule was introduced and a series of hybrid cross‐linked zwitterion‐containing copolymer DES gels are synthesized via UV initiated free‐radical copolymerization of acrylic acid (AA), sulfobetaine vinylimidazole (VIPS) and poly(ethylene glycol) diacrylate (PEGDA) monomers, in situ within DES, which is prepared from 1:2 M ratio of choline chloride and ethylene glycol. Systematically varying the AA:VIPS molar ratio and copolymer contents within the copolymer network enables one to widely tune the mechanical properties and ionic conductivity of the poly(AA‐ co ‐VIPS) DES gels. The tensile strength of P(AA‐ co ‐VIPS) DES gels significantly increased from 28 kPa to 176 kPa with fracture strain from 720% to 1370%, while the ionic conductivity of copolymer DES gels remains high from 2.7 to 4.1 mS cm −1 with the increase of copolymer content from 25 wt % to 45 wt%. A copolymer DES gel not only enables a supercapacitor deliver high capacitance of 71.52 F g −1 at 0.5 A g −1, and retains ∼97% of its capacitance after 2000 cycles, but also achieves outstanding capacitive performance over wide temperature range. Abstract : A highly stretchable deep eutectic solvent‐based ionic gel electrolyte with high ionic conductivity was designed and prepared by the addition of zwitterion ion dissociators for application in high‐performance flexible supercapacitor.